The Acute Effect of Repetitive Sprint Training on Some Biochemical Parameters in Futsal Players - Kahraman, Muhammed Zahit; Karadag, Alper; Bilici, Ömer Faruk; Okut, Sedat (Nazmi SARITAS, 2023)
The aim of this research is to determine the acute effect of repetitive sprint training on some biochemical parameters in futsal players. Ten male athletes (age: 21.50±1.84 years) in the futsal team of Mus Alparslan University voluntarily participated in the research. The research was designed with a pretest-posttest control group-free experimental design. 5 cc venous blood samples were taken from the athletes before and after the repetitive sprint training, and the samples were centrifuged at 4000 rpm for 10 minutes for biochemical analysis. After this process, serum blood samples were analyzed by photometric methods on the Architect ci16200 TM analyzer. The level of normality of the data was determined by the Shapiro-Wilk test. Paired sample t test was used to compare the pretest-posttest values of data with normal distribution, and Wilcoxon signed ranks test was used for those that did not provide the normality assumption. According to the research findings, a significant difference was determined between the pretest and posttest in glucose and creatinine values of futsal players (p<0.05). There was no significant difference between pretest and posttest values in urea, albumin, aspartate aminotransferase, alanine aminotransferase, lactate dehydrogenase, hemolysis, lipemia, icterus and gamma glutamyl transferase parameters (p>0.05). In glucose and creatinine parameters, it was determined that the posttest values of the futsal players were higher than the pretest values. As a result, it was determined that repetitive sprint training applied to futsal players had an acute effect on glucose and creatinine biochemical parameters. Understanding the effect and importance of biochemical parameters in futsal players can help coaches to prepare sportive performance and efficient training programs.

Bu arastirmanin amaci, futsal oyuncularinda tekrarli sprint antrenmaninin bazi biyokimyasal parametrelere akut etkisinin belirlenmesidir. Arastirmaya, Mus Alparslan Üniversitesi futsal takimindaki 10 erkek sporcu (yas: 21,50±1,84 yil) gönüllü olarak katilmistir. Arastirma, ön test-son test kontrol grupsuz deneysel desen ile tasarlanmistir. Sporculardan tekrarli sprint antrenmani öncesinde ve sonrasinda 5 cc venöz kan örnegi alinarak biyokimyasal analizler için numuneler 4000 rpm devirde 10 dk santrifüj edilmistir. Bu islemden sonra serum kan örnekleri Architect ci16200 TM analizöründe fotometrik yöntemlerle analiz edilmistir. Verilerin normallik düzeyi Shapiro-Wilk testi ile belirlenmistir. Normal dagilima sahip verilerin ön test-son test degerlerinin karsilastirilmasinda paired sample t testi, normallik varsayimini saglamayanlarda ise Wilcoxon isaretli siralar testi kullanilmistir. Arastirma bulgularina göre futsal oyuncularinin glukoz ve kreatinin degerinde ön test ile son testler arasinda anlamli bir fark belirlenmistir (p<0,05). Üre, albümin, aspartat aminotransferaz, alanin aminotransferaz, laktat dehidrogenaz, hemoliz, lipemi, ikter ve gama glutamil transferaz parametrelerinde ise ön test ile son test degerleri arasinda anlamli bir farklilik bulunmamistir (p>0,05). Glukoz ve kreatinin parametrelerinde futsal oyuncularinin son test degerlerinin ön test degerlerine göre yüksek oldugu tespit edilmistir. Sonuç olarak futsal oyuncularina uygulanan tekrarli sprint antrenmaninin glukoz ve kreatinin biyokimyasal parametreleri üzerinde akut etkisinin oldugu belirlenmistir. Futsal oyuncularinda biyokimyasal parametrelerin etkisini ve önemini anlamak, antrenörlere sportif performans ve verimli antrenman programlarinin hazirlanmasi için yardimci olabilir.
Futsal Oyuncularinda Tekrarli Sprint Antrenmaninin Bazi Biyokimyasal Parametrelere Akut Etkisi
Keywords: Sports Medicine; Spor Hekimligi